(untitled) (Journal of Parents and Teachers, 2026)
Since the MAT4 System was developed by Bernice Mc. Carthy in 1972 and through the continuous updates it has undergone, it has become an extremely useful resource for many teachers, who say they find in it a way to plan classroom learning, taking into account two fundamental aspects: the different ‘learning styles’ of each pupil and what is becoming known about how the two cerebral hemispheres function. In short, it addresses how people learn and, consequently, how we can improve. It is based on the most recent studies in psychology, neurology and human behaviour modification.